2014
DOI: 10.1242/jcs.151472
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial cell division – multiplying without losing touch

Abstract: Epithelia are compact tissues comprising juxtaposed cells that function as mechanical and chemical barriers between the body and the environment. This barrier relies, in part, on adhesive contacts within adherens junctions, which are formed and stabilized by Ecadherin and catenin proteins linked to the actomyosin cytoskeleton. During development and throughout adult life, epithelia are continuously growing or regenerating, largely as a result of cell division. Although persistence of adherens junctions is need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 136 publications
3
18
0
Order By: Relevance
“…In solid organs, dividing cells are part of tissues, and recent studies suggest that in addition to intracellular events, successful cytokinesis requires coordination with extracellular processes (Herszterg et al, 2014; Le Bras and Le Borgne, 2014). For instance, cooperation between dividing cells and their neighbors is necessary to remodel cell adhesion during cytokinesis while maintaining tissue cohesiveness (Founounou et al, 2013; Guillot and Lecuit, 2013; Herszterg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In solid organs, dividing cells are part of tissues, and recent studies suggest that in addition to intracellular events, successful cytokinesis requires coordination with extracellular processes (Herszterg et al, 2014; Le Bras and Le Borgne, 2014). For instance, cooperation between dividing cells and their neighbors is necessary to remodel cell adhesion during cytokinesis while maintaining tissue cohesiveness (Founounou et al, 2013; Guillot and Lecuit, 2013; Herszterg et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It has been intensively investigated in drosophila17181920, but the mechanisms by which this process is driven, in term of molecular tension and membrane deformation, are not well understood2122. Is cadherin stretched by actomyosin at adherens junction to create membrane tension and deformation?…”
mentioning
confidence: 99%
“…68,69 This has been better defined during cytokinesis and abscission of the 2 nascent daughter cells. In Drosophila, it has been observed that the levels of AJs are reduced at the cleavage furrow of dividing cells.…”
Section: Links Between Cadherin-catenins and Positioning Of Mitotic Smentioning
confidence: 99%